Sales funnel in marketing - Markina, A. (My University, 2021)
In marketing exists a tool, or process, which shows the way a potential customer takes from the moment when he is not even interested yet and until he makes the purchase - this is called the sales funnel. The aim of this article is to explore the sales funnel, its steps, and how it works, and why it is necessary for business.
Keywords: marketing; sales funnel; business